Islamic Boarding School Culture In Developing The Character of Students - Afidah, Briliana; Goffar, Abdul (JIEM (Journal of Islamic Education Management), 2024)
This study aims to describe the culture of Islamic boarding school in developing the character of students. This research method uses a qualitative approach with a Phenomenological research type. Data collection techniques use interviews, observations and documentation. The subjects in this study include: caregivers, deputy caregivers, foundation heads, Teachers and students. While the data analysis used is the Miles and Huberman interactive model. The results of this study; 1) The culture that becomes a forum for habituation in developing the character of students is Covert Culture which consists of ta'dzim, 5S, uswah hasanah, practice and habituation, Mauidah, Ibrah, targib wa tahzib. (2) The character values that develop are in line with the Concept of the Strengthening Character Education Program (PPK) and the Pancajiwa pesantren which consists of Religion, Independence, Simplicity, Ukhuwah, Mutual Cooperation, Integrity, Sincerity, Nationalism. The application of Islamic boarding school culture has broad implications for the development of the character of students. Islamic boarding schools not only produce knowledgeable individuals, but also form people who are independent, responsible, have good morals, and are ready to make a positive contribution to society.Keyword: Islamic School culture, Character Development, Student Penelitian ini bertujuan untuk mendeskripsikan budaya pesantren dalam pengembangan karakter santri. Metode penelitian ini menggunakan Pendekatan kualitatif dengan jenis penelitian Fenomenologi. Tehnik pengumpulan data menggunakan wawancara, observasi dan dokumentasi. Subjek dalam penelitian ini meliputi: pengasuh, wakil pengasuh, ketua yayasan, ustadz dan santri. Sedangkan analisis data yang digunakan ialah model interaktif Miles dan Huberman. Hasil penelitian ini; 1) Budaya yang menjadi wadah pembiasaan dalam mengembangkan karakter santri ialah Covert Culture yang terdiri dari ta'dzim, uswah hasanah, Latihan dan pembiasaan, Mauidah, Ibrah, targib wa tahzib. (2) Nilai – Nilai karakter yang berkembang sejalan dengan Konsep Program Penguatan Pendidikan Karakter (PPK) dan Pancajiwa pesantren yang terdiri dari Religius, Kemandirian, Kesederhanaan, Ukhuwah, Gotong Royong, Integritas, Keikhlasan, Nasionalis. Penerapan budaya pesantren memiliki implikasi luas bagi pengembangan karakter santri. Pesantren tidak hanya mencetak individu yang berilmu, tetapi juga membentuk manusia yang mandiri, bertanggung jawab, berakhlak mulia, dan siap berkontribusi positif di masyarakat.Kata Kunci : Budaya Pesantren, Pengembangan Karakter, Santri